Tantangan dalam Mengadaptasi Teknologi Wolbachia untuk Pengendalian Demam Berdarah - Luh Herry Novayanti; Ni Wayan Whidhiastini (Postgraduate, University of Mataram, 2025)
The global increase in dengue cases has prompted the development of the Wolbachia method as an innovative vector control strategy. In response, the Indonesian Government, through the Ministry of Health, has implemented the Wolbachia method in various regions. The application of this novel strategy requires cross-sectoral collaboration to enhance implementation effectiveness. This qualitative study aims to analyze the implementation of the Wolbachia program in Buleleng Regency, Bali, within a multi-stakeholder collaborative framework. Data was gathered through in-depth interviews and document reviews to investigate the dynamics and challenges of collaboration. The findings reveal significant obstacles to effective collaboration, including weak communication, overlapping roles, bureaucratic complexity, and regulatory deficiencies. These issues have adversely affected community participation and led to resistance toward the program. The study contributes to the public policy implementation literature by highlighting the critical need for clear communication, defined roles, and technical guidelines to improve implementation success. It recommends enhancing communication, coordination, regulation, and misinformation mitigation to optimize cross-sectoral collaboration in the execution of innovative public health policies.